The future of the world's climate - Henderson-Sellers, Ann and McGuffie, Kendal (Elsevier, 2012)
"The study of climate today seems to be dominated by global warming, but these predictions of climatic models must be placed in their geological, paleo-climatic, and astronomical context to create a complete picture of the Earth's future climate. The Future of the World's Climate presents that perspective with data and projections that have emerged from more technologically advanced and accurate climate modeling"--Publisher's website.